2011
DOI: 10.1055/s-0031-1279719
|View full text |Cite
|
Sign up to set email alerts
|

ACL Injury Mechanisms and Related Factors in Male and Female Carving Skiers: A Retrospective Study

Abstract: In recreational alpine skiing, ACL injury risk is 3 times greater in females. However, since the introduction of carving skis ACL injury risk seems to have decreased. No study has yet investigated the distribution of ACL injury mechanisms in male and female carving skiers. Therefore, the aim of the study was to investigate potential gender specific differences of ACL injury mechanisms and related factors among carving skiers. In total, 220 recreational carving skiers (59 males and 161 females) suffering from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
57
2
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 52 publications
(75 citation statements)
references
References 30 publications
11
57
2
5
Order By: Relevance
“…In our tests, 84% of female trials and 54% of male trials showed a failure of selfrelease of their ski bindings. These sex-specific values seem in line with findings observed among ACL-injured recreational skiers where 74-88% of female skiers compared to 55-67% male skiers reported a failure of binding to release [9][10][11][12]. This conformity might be somewhat surprising as the self-release test was performed in a stationary laboratory setting in contrast to the self-reported amount of failure of binding release during skiing on the slope leading to an ACL injury.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…In our tests, 84% of female trials and 54% of male trials showed a failure of selfrelease of their ski bindings. These sex-specific values seem in line with findings observed among ACL-injured recreational skiers where 74-88% of female skiers compared to 55-67% male skiers reported a failure of binding to release [9][10][11][12]. This conformity might be somewhat surprising as the self-release test was performed in a stationary laboratory setting in contrast to the self-reported amount of failure of binding release during skiing on the slope leading to an ACL injury.…”
Section: Discussionsupporting
confidence: 85%
“…No increase in injuries from inadvertent binding release through reduced binding settings has been found [21]. However, these findings mean an association, and not definitely "cause and effect" relationship, because another study at the same time showed a decrease in ACL injury risk without reducing binding settings [22] which might be due to the introduction of the short and shaped carving skis at this time [11]. Interestingly, the ISO 11088 standard accepts a deviation of 15% between the measured release moment ("reference moment") determined according to the setting tables in ISO 8061 and ski binding settings may also be lowered by the same magnitude upon request of the skier [23].…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations